LASIK world literature review: quality of life and patient satisfaction - Solomon, Kerry D; Fernández de Castro, Luis E; Sandoval, Helga P; Biber, Joseph M; Groat, Brian; Neff, Kristiana D; Ying, Michelle S; French, John W; Donnenfeld, Eric D; Lindstrom, Richard L (Ophthalmology (Rochester, Minn.), 2009)
To analyze the patient reported outcome of satisfaction after LASIK surgery. Systematic review. Patient data from previously reported studies. A literature search conducted for the years 1988 to 2008 that included pertinent LASIK surgery information from the review of 2915 retrieved citations. All abstracts from these citations were reviewed and 1581 were deemed to be relevant for review. Complete copies of each of these relevant (1581) articles were obtained, and after thorough analysis each was rated based on the strength of the study design and weight of evidence. A level I rating was assigned to properly conducted, well-designed, randomized clinical trials; a level II rating to well-designed cohort and case-control studies; and a level III rating to case series, case reports, and poorly designed prospective and retrospective studies. Level I and II rated, peer-reviewed articles were entered into a database, and level III articles were eliminated. A total of 309 articles were incorporated into this database, representing level I and level II well-controlled studies of primary LASIK surgery. Patients' satisfaction rates and factors associated with dissatisfaction. Nineteen of the 309 database articles (6.1%) reported on both patient quality of life and satisfaction and together encompassed a total of 2198 subjects. The procedures from these 19 articles took place between 1995 and 2003. The overall patient satisfaction rate after primary LASIK surgery was 95.4% (2097 of 2198 subjects; range of patient satisfaction for the 19 articles was 87.2%-100%). The patient satisfaction rate after myopic LASIK was 95.3% (1811 of 1901 patients), and after hyperopic LASIK was 96.3% (286 of 297 subjects). Based on this review, worldwide, an average 95.4% of patients were satisfied with their outcome after LASIK surgery. With 16.3 million procedures performed worldwide, and more than a decade of clinical studies and technological innovation, LASIK surgery should be considered among the most successful elective procedures. LASIK surgery compares more favorably with other elective surgical procedures in terms of generally higher satisfaction rates.